Christian-Muslim Relations. A Bibliographical History Volume 23. Russia (1800-1914) - Chesworth, John,; Grodź, Stanisław,; Pratt, Douglas,; Soldat, Cornelia,; Thomas, David, (Middle East and Islamic Studies E-Books Online, Collection 2024., 2025)
Christian-Muslim Relations, a Bibliographical History 23 (CMR 23), covering Russia, in the period 1800-1914, is a further volume in a general history of relations between the two faiths from the 7th century to the early 20th century. It comprises a series of introductory essays and the main body of detailed entries. These treat all the works, surviving or lost, that have been recorded. They provide biographical details of the authors, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between numerous new and leading scholars, CMR 23, along with the other volumes in this series, is intended as a fundamental tool for research in Christian-Muslim relations. Section Editors: Ines Aščerić-Todd, Clinton Bennett, Luis F. Bernabé Pons, Jaco Beyers, Emanuele Colombo, Lejla Demiri, Martha T. Frederiks, David D. Grafton, Stanisław Grodź, Alan M. Guenther, Vincenzo Lavenia, Arely Medina, Diego Melo Carrasco, Alain Messaoudi, Gordon Nickel, Claire Norton, Reza Pourjavady, Douglas Pratt, Charles Ramsey, Peter Riddell, Umar Ryad, Cornelia Soldat, Charles Tieszen, Carsten Walbiner, Catherina Wenzel